FAKTOR-FAKTOR YANG MEMPENGARUHI NIAT MELAKUKAN PENGGELAPAN PAJAK - Yuliani Karlina; Asep Kurniawan; Indah Umiyati (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2021)
Indonesia is a developing country that needs funds to finance its development. In order to finance all the interests of the state in realizing a better national economy, an APBN (State Revenue and Expenditure Budget) is prepared. The taxation sector is the largest sector that contributes to the State Budget. However, in the implementation of tax revenue does not match the predetermined target, one of the causes of this is due to tax evasion by taxpayers. This study aims to examine the factors that influence the intention to commit tax evasion. This research is a quantitative research with data collection techniques using a questionnaire distributed to taxpayers who are registered free workers at KPP Pratama Subang. The sample used in this study was 118 respondents using purposive sampling technique and an error rate of 5%. The analysis technique uses multiple linear regression analysis. The results showed that the coefficient of determination R2 was 0.374, which means that the dependent variable could be explained by the independent variable at 37.4% and the remaining 62.6% was explained by other variables. The results of this study conclude that partially the variable love of money, tax system, tax justice, tax discrimination, and tax sanctions has no effect on tax evasion, while the variable understanding of taxation has a negative effect on tax evasion and the variable religiosity has a negative effect on tax evasion. Simultaneously, the variable love of money, tax system, tax justice, tax discrimination, understanding of taxation, taxation sanctions and religiosity have an effect on the variable tax evasion.